The importance of institutional and organizational characteristics for the use of fixed-term and agency work contracts in Russia - L. I. Smirnych; Andreas Wörgötter (Vienna University of Technology, Institute of Statistics and Mathematical Methods in Economics, Research Group Economics, 2016)
Non-renewable fixed-term and agency work contracts are becoming more used instead of the traditional Russian model of open-ended employment. The authors examine the influence of institutional and organizational factors on the use of two forms of non-standard work contracts in Russia with data from a Survey covering 3313 enterprises for the years 2009 to 2011. Probit and Tobit regressions are used to test several hypotheses about the use of non-standard work contracts derived from the literature. The results indicate that state-owned and unionized enterprises are more likely to use fixed-term contracts; and a high level of perceived dismissal protection for permanent workers is positively associated with fixed-term contracts use. The incidence and intensity of fixed-term and agency work contracts are lower at enterprises with flexible wages. A significant impact of organizational factors is confirmed only for fixed-term contracts. Enterprises use less fixed-term contracts, if they have workers with tenure from 5 to 10 years and high job complexity.
Keywords: J41; J21; J63; J23; 330; fixed-term contracts; agency work; non-standard employment; labor flexibility; Russia